1993
DOI: 10.1021/jf00025a023
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial activity against Streptococcus mutans of mate tea flavor components

Abstract: The 10 major volatile constituents were identified by GC-MS analysis as common flavor principles in mate tea obtained from various locations. Their antimicrobial activity against 13 microorganisms was tested. All of the volatiles tested exhibited moderate to weak activity with broad spectra. Some of them are bactericidal against one of the most important cariogenic bacteria, Streptococcus mutans. The antibacterial activity of the distillate against S. mutans was significantly enhanced by indole.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
68
0
4

Year Published

1995
1995
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(72 citation statements)
references
References 9 publications
0
68
0
4
Order By: Relevance
“…Relatively limited research has been conducted on isolation and identification of compounds possessing antimicrobial activity derived from yerba mate (Kubo et al, 1993;Hongpattarakere, 2000;Sari et al, 2007;Tsai et al, 2008;Filip et al, 2010). Filip et al (2010) identified caffeoyl derivatives, methylxanthines, and rutin from yerba mate aqueous extracts with antifungal activity.…”
Section: Bioactive Properties and Health Implications Antimicrobial Amentioning
confidence: 99%
See 3 more Smart Citations
“…Relatively limited research has been conducted on isolation and identification of compounds possessing antimicrobial activity derived from yerba mate (Kubo et al, 1993;Hongpattarakere, 2000;Sari et al, 2007;Tsai et al, 2008;Filip et al, 2010). Filip et al (2010) identified caffeoyl derivatives, methylxanthines, and rutin from yerba mate aqueous extracts with antifungal activity.…”
Section: Bioactive Properties and Health Implications Antimicrobial Amentioning
confidence: 99%
“…50 g of packed tea. The beverage is then drunk by using a metal straw or "bombilla", which has small holes that prevent the leaves from being consumed (Kubo et al, 1993;Heck and de Mejia, 2007;Heck et al, 2008).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Nos primeiros estudos de óleos da erva-mate, Kubo et al, (1993) veri caram a atividade antimicrobiana, dos constituintes voláteis do óleo essencial da erva-mate processada, e atribuíram ao linalol, composto mais abundante, ação moderada contra a bactéria Streptococcus mutans. Em relação ao linalol, também é reportada a importante atividade antifúngica, anti-helmíntica (Henriques et al, 2007) e ação anticonvulsiva (Brum et al, 2001).…”
unclassified